Identification of biomarkers associated with sexual maturity in laying hens based on metabolomics and gut microbiology - Han Yaxiao; Zhang Ran; Zhou Rongyan; Zhang Zhenhong; Zhang Yinliang; Yu Shulong; Li Lanhui (Poultry Science, 2025)
Sexual maturation is an important trait in poultry production. The initiation mechanism of sexual maturity is significant for breeding high-yield laying hens. Plasma metabolomics and gut microbiology were used to identify biomarkers of sexual maturity in laying hens. Cecal contents and plasma samples were collected from laying hens at 15 w, 17 w, and 22 w during the sexual maturity transition period. A total of 208 differential metabolites are significantly enriched pathways of sphingolipid metabolism, glycine, serine, and threonine metabolism between 15 w and 17 w. A total of 183 differential metabolites were significantly enriched pathways of valine, leucine, isoleucine biosynthesis and glycerophospholipid metabolism between 17 w and 22 w. A total of 56 potential biomarkers, mainly consisting of carnitine and choline metabolites, was identified for the transition from 15 w to 22 w with the receiver operating characteristic (ROC) curve analysis. A positive correlation between metabolites and estrogen was identified through Weighted Gene Co-expression Network Analysis (WGCNA). The bacterial taxa associated with sexual maturity were identified in hens at three week-of-age by 16S rDNA Amplicon Sequencing. The bacterial compositions of 15 w, 17 w, and 22 w are distinct, with their main bacterial genera being Bacteroidetes, Desulfovibrio, and Lactobacillus, respectively. The bacterial species enriched in the three groups were key biomarkers distinguishing sexual maturity and significantly correlated with the shifts in the functional capacities of the gut microbiome. The choline, betaine, and methionine in metabolites are correlated with different bacteria using joint analysis, indicating that microbial communities can affect host metabolism. These results provide important insights into the dynamic change of plasma metabolism and gut microbiome in laying hens.